Endothelial Cell–Derived Von Willebrand Factor, But Not Platelet-Derived, Promotes Atherosclerosis in Apolipoprotein E–Deficient Mice. Issue 3 (March 2018) - Doddapattar, Prakash; Dhanesha, Nirav; Chorawala, Mehul R.; Tinsman, Chandler; Jain, Manish; Nayak, Manasa K.; Staber, Janice M.; Chauhan, Anil K.
Abstract : Objective—: VWF (von Willebrand factor) is synthesized by endothelial cells and megakaryocytes and is known to contribute to atherosclerosis. In vitro studies suggest that platelet-derived VWF (Plt-VWF) is biochemically and functionally different from endothelial cell–derived VWF (EC-VWF). We determined the role of different pools of VWF in the pathophysiology of atherosclerosis. Approach and Results—: Using bone marrow transplantation, we generated chimeric Plt-VWF, EC-VWF, and Plt-VWF mice lacking a disintegrin and metalloprotease with thrombospondin type I repeats-13 in platelets and plasma on apolipoprotein E–deficient ( Apoe −/− ) background. Controls were chimeric Apoe −/− mice transplanted with bone marrow from Apoe −/− mice (wild type) and Vwf −/− Apoe −/− mice transplanted with bone marrow from Vwf −/− Apoe −/− mice (VWF-knock out). Susceptibility to atherosclerosis was evaluated in whole aortae and cross-sections of the aortic sinus in female mice fed a high-fat Western diet for 14 weeks. VWF-knock out, Plt-VWF, and Plt-VWF mice lacking a disintegrin and metalloprotease with thrombospondin type I repeats-13 exhibited reduced plaque size characterized by smaller necrotic cores, reduced neutrophil and monocytes/macrophages content, decreased MMP9 (matrix metalloproteinase), MMP2, and CX3 CL1 (chemokine [C-X3-C motif] ligand 1)-positive area, and abundant interstitial collagen ( P <0.05 versus wild-type or EC-VWF mice). Atherosclerotic lesion size and composition were comparable between wild-type or EC-VWF mice. Together these findings suggest that EC-VWF, but not Plt-VWF, promotes atherosclerosis exacerbation. Furthermore, intravital microscopy experiments revealed that EC-VWF, but not Plt-VWF, contributes to platelet and leukocyte adhesion under inflammatory conditions at the arterial shear rate. Conclusions—: EC-VWF, but not Plt-VWF, contributes to VWF-dependent atherosclerosis by promoting platelet adhesion and vascular inflammation. Plt-VWF even in the absence of a disintegrin and metalloprotease with thrombospondin type I repeats-13, both in platelet and plasma, was not sufficient to promote atherosclerosis. Abstract : Supplemental Digital Content is available in the text.